Tough, Reprocessable, and Recyclable Dynamic Covalent Polymers with Ultrastable Long‐Lived Room‐Temperature Phosphorescence - Zhao, Zi‐Han; Zhao, Pei‐Chen; Chen, Shi‐Yi; Zheng, You‐Xuan; Zuo, Jing‐Lin; Li, Cheng‐Hui (Angewandte Chemie International Edition, 2023)
Room‐temperature phosphorescence (RTP) polymers, whose emission can persist for a long period after photoexcitation, are of great importance for practical applications. Herein, dynamic covalent boronic ester linkages with internal B−N coordination are incorporated into a commercial epoxy matrix. The reversible dissociation of B−N bonds upon loading provides an efficient energy dissipation pathway for the epoxy network, while the rigid epoxy matrix can inhibit the quenching of triplet excitons in boronic esters. The obtained polymers exhibit enhanced mechanical toughness (12.26 MJ m−3), ultralong RTP (τ=540.4 ms), and shape memory behavior. Notably, there is no apparent decrease in the RTP property upon prolonged immersion in various solvents because the networks are robust. Moreover, the dynamic bonds endow the polymers with superior reprocessablity and recyclability. These novel properties have led to their potential application for information encryption and anti‐counterfeiting. Incorporating dynamic covalent boronic ester linkages with internal B−N coordination into a commercial epoxy matrix has led to the fabrication of high‐performance polymer‐based materials with ultralong room‐temperature phosphorescence. The polymers show excellent mechanical properties, environmental stability, shape memory, and recyclability, which could be useful for anticounterfeiting, data encryption, and information editing applications.